The Role of Traditional Medicine in Antibiotic Resistance - og’li, Bahodirov Behruz Shavkat (American Journal of Bioscience and Clinical Integrity, 2024)
Antibiotics can undoubtedly save millions of lives, but at the same time, they can also cause harm, even to future generations, if used improperly! This once again raises the issue of the rational use of antibacterial agents and highlights the fact that, despite all efforts, there is a lack of knowledge in the global medical community about the potentially harmful aspects of antibiotic therapy. Ethiopian colleagues report on the irrational use of antibiotics, far from WHO recommendations, predominantly in injectable forms.